Wino i technologia produkcji win w Gallii Narbonensis w II w. p.n.e. – II w. n.e. - Góralczyk, Agnieszka (Folia Praehistorica Posnaniensia, 2020)
The article describes the process of making wine in antiquity and tools used for it. It presents wine production in the Roman province of Gallia Narbonensis based on historical and archaeological sources.